A Bibliometric Analysis of Global Research Trends in Polycystic Ovary Syndrome and Metformin - Bowen Tang; Tao Tan; Yi Huang; Mi Zhang; Mengqing Li; Xiaocan Lei; Weihua Nong (IMR Press, 2024)
Background: Polycystic ovary syndrome (PCOS) stands as one of the most prevalent endocrine disorders affecting women of reproductive age. Despite being recognized for decades, numerous unresolved issues persist regarding its impact on reproductive medicine. Metformin, a widely utilized drug in clinical practice for PCOS management, has attracted researchers' attention due to its pharmacological mechanism and novel drug combination methods. Methods: This study employs bibliometric analysis to comprehensively examine the research progress in this field. The statistical source for this paper is Web of Science, covering the entire timespan. Utilizing various tools such as Web of Science, VOSviewer, and CiteSpace for analysis, the focus is on countries, institutions, authors, journals, and keywords. Data encompass the total number of papers published, total citations, and the average number of citations per paper. Results: Our analysis uncovered 2817 papers within the statistical range, with both paper count and citations exhibiting a rising trend over the years. The United States, China, and the United Kingdom emerged as influential countries in this field. Primary research areas include molecular biology, immunology, and clinical medicine. While China has made significant progress in recent years, there is room for improvement in the average number of citations per article, highlighting the importance of emphasizing article quality. Conclusions: The United States has spearheaded research in this field, potentially owing to support from domestic universities. Nevertheless, the notable contribution of Chinese scientists cannot be overlooked. Among universities, the most prolific are the Federal University of Virginia from United States and Fudan University from China. Notably, Glueck CJ is identified as the most productive researcher in this field. Fertility and Sterility, ranking first globally in terms of both article count and citations, emerges as the most popular journal in this field.